2018
DOI: 10.1071/an16184
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and relationship between meat colour and antioxidant capacity of different pig breeds

Abstract: The objectives of this study were to evaluate meat colour, antioxidant performance of longissimus muscle in different pig breeds, including five Chinese native pig breeds, a Chinese bred pig breed as well as a commercial crossbred pig breed, and to analyse the relationships between meat colour and antioxidant capacity. The results showed that the Chinese native and bred pig breeds have higher meat colour and marbling scores than commercial crossbred pigs. The Chinese native and bred pig breeds showed significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…The extent of lipid peroxidation was also the lowest in Laiwu pig samples as revealed by the MDA content. The result agrees with our previous studies, where the Laiwu pig breeds showed higher total antioxidant capacity and superoxide dismutase activity than commercial crossbred pigs (Chen et al., , ).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…The extent of lipid peroxidation was also the lowest in Laiwu pig samples as revealed by the MDA content. The result agrees with our previous studies, where the Laiwu pig breeds showed higher total antioxidant capacity and superoxide dismutase activity than commercial crossbred pigs (Chen et al., , ).…”
Section: Resultssupporting
confidence: 93%
“…The Chinese native pig breeds are very important recourses for improving the pork quality for meeting the demand of the consumers. Our previous research shows that the Chinese native pig breeds had good meat quality and also had stronger antioxidant capacity than western pig breeds (Chen et al., , ). Currently, there is little information available on the pH u as a predictor to explain the variation of antioxidant capacity in pigs; therefore, this study was designed to determine the effects of pH u on activity of antioxidant enzymes, MDA content, and gene expression, and also to characterize the relationship between pH u and antioxidant capacity in pigs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zhang et al (2015b) suggested that Chinese rongchang pig exhibited greater IMF, pH 45min , pH 24h compared with the Landrace pig. Chen et al (2018) reported that Chinese local pig breeds (laiwu pig, Lulai pig, Wulian pig, Yantaipig and Yimeng pig) have better meat colour than commercial crossbreed pig DLY. Similar results of meat sensory quality were also found in the Anqingliubai and the Yorkshire pigs, which suggested that the Anqiuliubai pigs had greater meat sensory quality than that in the Yorkshire pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the Jinhua pig (Guo et al 2011;Miao et al 2009), Meishan pig (Suzuki et al 1991), Taihu pig (Li et al 2008), and Min pig (Liu et al 2017) showed better meat sensory quality compared with the Landrace pig, Duroc × Landrace pig, Landrace pig, and Yorkshire pig, respectively. It has been demonstrated that lipid oxidation affected the sensory quality in the post-slaughter meat of pig (Chen et al 2018). MDA is one of the important circulating indicators which reflect the degree of lipid oxidation in muscle (Lykkesfeldt and Svendsen 2007;Del Rio et al 2005).…”
Section: Discussionmentioning
confidence: 99%